CS21 positive multidrug-resistant ETEC clinical isolates from children with diarrhea are associated with self-aggregation, and adherence - Cruz-Córdova, Ariadnna; Espinosa-Mazariego, Karina; Ochoa, Sara A.; Saldaña, Zeus; Rodea, Gerardo E.; Cázares-Domínguez, Vicenta; Rodríguez-Ramírez, Viridiana; Eslava-Campos, Carlos A.; Navarro-Ocaña, Armando; Arrellano-Galindo, José; Hernández-Castro, Rigoberto; Gómez-Duarte, Oscar G.; et al. (Frontiers in Microbiology, 2014)
Background: Enterotoxigenic Escherichia coli (ETEC) colonize the human intestinal mucosa using pili and non-pili colonization factors (CFs). CS21 (also designated Longus) is one of the most prevalent CFs encoded by a 14 kb lng DNA cluster located in a virulence plasmid of ETEC; yet limited information is available on the prevalence of CS21 positive ETEC isolates in different countries. The aim of this study was to evaluate the prevalence of CS21 among ETEC clinical isolates from Mexican and Bangladeshi children under five years old with diarrhea and to determine the phenotypic and genotypic features of these isolates. Methods: ETEC clinical isolates positive to lngA gene were characterized by genotype, multidrug-resistance, self-aggregation, biofilm formation and adherence to HT-29 cell line. Results: A collection of 303 E. coli clinical isolates were analyzed, the 81.51% (247/303) were identified as ETEC, 30.76% (76/247) were st+/lt+, and 25.10% (62/247) were positive for the lngA gene. Among the lngA+ ETECs identified, 50% of isolates (31/62) were positive for LngA protein. The most frequent serotype was O128ac:H12 found in 19.35% (12/62) of lngA+ ETEC studied. Multidrug-resistance (MDR) lngA+ ETEC isolates was identified in 65% (39/60), self-aggregation in 48.38% (30/62), and biofilm formation in 83.87% (52/62). ETEC lngA+ isolates were able to adhere to HT-29 cells at different levels. Two lngA isogenic mutants were constructed in the ETEC E9034A and ETEC73332 clinical isolate, showing a 77% and 98% reduction in adherence respectively with respect to the wild type. Conclusion: ETEC isolates that har the lngA gene showed features associated with self-aggregation, and adherence to HT-29 cells important characteristics in the human gut colonization process and pathogenesis.